Disseminating clot burden post- craniotomy: The difficult balancing act of clot versus haemorrhage post-neurosurgery - Bowcock, Emma; Morris, Idunn; Lane, Stuart (Journal of Neuroanaesthesiology and Critical Care, 2016)
Venous thromboembolism (VTE) is the most common complication following craniotomy for neoplastic disease. Its occurrence is associated with a significant morbidity and mortality, and balancing the risks for the subsequent development of VTE versus intracranial haemorrhage (ICH) can lead to difficult management decisions for treating clinicians. We present a case of VTE following craniotomy for meningioma complicated by ICH in the presence of a disseminating clot burden that included pulmonary, intra-cardiac and paradoxical arterial embolic sequelae. Management strategies incorporated pharmacological, radiological and surgical methods. We discuss the evidence for VTE prevention and treatment, as well as the role of inferior vena cava filters and thrombectomy. We finally highlight the use of desmopressin as a potential risk factor for VTE, and encourage the need for an individualised approach to peri-operative risk stratification in the neurosurgical intensive care population.
Keywords: Anticoagulation; inferior vena cava filter; neurosurgical intensive care; thrombectomy; venous thromboembolism